Amphibian fauna of Bahrain - Aaron M., Bauer; Indraneil, Das (Springer Nature, 2025)
The Kingdom of Bahrain is an insular nation, lying between latitudes 25.6° and 26.3° N and longitudes 50.3° and 50.8° E, and is the third smallest country in Asia, covering a land area of 780 km2 (including 115 km2 in reclaimed land in the form of artificial islands). A single species of amphibian has been recorded- the Marsh Frog, Pelophylax ridibundus. The species is widespread from much of Western and Central Europe to trans-Ural Russia and south to Afghanistan and parts of Iran. Scattered areas in Saudi Arabia represent the southernmost extent of the species and include the nearest mainland locality to Bahrain at a distance of approximately 25 km.